Gender Bias in AI: Tackling Inequality in Machine Learning Models (Journal of responsible AI & ethics, 2026)
Artificial intelligence has become a powerful technological force shaping decision-making systems in modern society. From hiring platforms and credit approval systems to healthcare diagnostics and facial recognition technologies, machine learning models increasingly influence human opportunities and social outcomes. However, the growing dependence on algorithmic decision-making has also exposed significant ethical challenges, among which gender bias remains one of the most pressing concerns. Gender bias in artificial intelligence refers to the systematic and unfair discrimination embedded within machine learning models that produce unequal outcomes for individuals based on gender. These biases often arise due to imbalanced training datasets, historical societal inequalities, and flawed model design practices. When such biases remain unaddressed, AI systems can reinforce existing gender inequalities rather than eliminate them. This research paper investigates the origins, mechanisms, and impacts of gender bias in machine learning systems while exploring effective strategies for mitigating algorithmic discrimination.